Environmental pollutants and marine mammal health: The potential impact of hydrocarbons and halogenated hydrocarbons on immune system dysfunction - Busbee, David; Tizard, Ian; Sroit, Jeffrey; Ferrirc, Davide; Orr-reeves, Ellen (J. Cetacean Res. Manage., 2020)
This paper provides a detailed review of the immunotoxicological effects of environmental pollutants on the health of marine mammals, particularly in relation to their impact on the immune system and mechanisms of toxicity. Environmental pollutants are increasingly implicated (both directly and indirectly) with the onset of infectious disease and related mortality incidents in marine mammals,. The release of chemicals into the marine environment and the subsequent bioaccumulation up the food chain may pose a serious threat to marine mammals inhabiting contaminated areas; this has been documented in various studies of pollutant concentrations in tissue samples and large scale mass mortalities. Data correlating pollutant residues with altered reproductive/developmental states, and immune system dysfunction in particular, are reported for terrestrial mammals and suggest a similar association in marine mammals. Immunology is emphasised as a tool for assessing marine mammal health using quantitative and qualitative techniques to establish the effects of chemical pollutants. This has become increasingly important in relation to the subsequent dangers that may be posed to humans through any indirect exposure via the food chain.